Ekstrak Metanol Biji Asam Jawa (Tamarindus Indica) Memperbaiki Kerusakan Histopatologi Ginjal Tikus yang Diinduksi Aluminium - Anang Dwi Atmoko; Al Munawir; Ika Rahmawati Sutejo (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2020)
Aluminum is the most widely used metal in everyday and the exposure of aluminum can be accumulate in kidney tubular cells, which cause tubular cell degeneration through oxidative stress because of nephrotoxicity. Tamarindus indica seeds contain high polyphenolic compounds and high antioxidant potential. This study aimed to investigate whether the methanolic extract of Tamarindus indica seeds repair histopathological damage of aluminum-induced kidney rat assessed by the parameters of tubular cell degeneration and necrosis. This experimental study was conducted at the Faculty of Medicine, University of Jember for 10 weeks using 30 male Wistar rats. Rats were divided into 5 groups; 1) K: control group was given a mixture of aquabides-saline (NaCl 0.9%), 2) K (-): negative control group was given aluminum solution (AlCl3), 3) P1: first treatment group was given aluminum solution (AlCl3) and extract (25 mg/kg b.w., po),  4) P2: second treatment group was given aluminum solution (AlCl3) and extract (50 mg/kg b.w., po), 5) P3: third treatment group was given aluminum solution (AlCl3) and extract (100 mg/kg b.w., po). Aluminum solution is given in a dose of 300 mg/kg b.w. po. After being terminated, the rat’s kidney histology were examined to a scoring damage process. Based on cell degeneration parameter, all groups get 5 in score of damage. Meanwhile based on cell necrosis parameter, all group get different score of damage. Based on the cell necrosis parameter, the methanolic extract of Tamarindus indica seeds repair histopathological damage of rat kidney induced by aluminum chloride